INCLUSÃO E FORMAÇÃO DOCENTE - Maria Odete Emygdio da Silva (EccoS – Revista Científica)
Today's schools are challenged to the problem-solving of many situations, v.g. multiculturalism or inclusion of students with special educational needs, which call for the implementation of distinct practices, based on cooperation and inclusive differentiation, that will contribute to significant apprenticeships. Schools are a privileged place for the interaction of policies, of cultures and of practices. We therefore consider of utmost importance to ponder over the effectiveness of implementing activities to the facilitation of said interaction and to a significant bearing of inclusion. The findings of the research we have been carrying out, some of which are present in this article, as well as the practice in which we have been involved, show how training based on the analysis of needs is an excellent contribution to examining these and other questions aroused by the inclusion these students.